UJI AKTIVITAS ANTIBAKTERI YOGHURT LABU KUNING (cucurbita moschata Durch) TERHADAP BAKTERI Escherichia coli dan Salmonella thypi - wahyu utami (Jurnal Penelitian Farmasi Indonesia, 2017)
ABSTRACT Synbiotic yoghurt is one of the functional food products of fermented milk containing good bacteria. Sinbiotic is a combination of probiotics and prebiotics. This study aims to determine the antibacterial activity of synbiotic yoghurt yellow pumpkin (Cucurbita moschata Durch) in inhibiting bacteria Escherichia coli and Salmonella thypi. This study used a complete randomized design (RAL) consisting of 3 treatments, namely the addition of sucrose with concentrations (10%, 15%, 20%) and 3 replications. The conclusion of this research shows that the formula of yoghurt with sucrose addition of 15% (F2) produces the desired yoghurt characteristic and has fulfilled the quality standard of SNI yoghurt (2981: 2009) with the result of hedonic test of panelist gives the value of likes to likes to color , aroma, taste and texture; for color (pale yellow), aroma (typical), taste (slightly acid), texture (slightly thick); degree of acidity (pH) 3,5; total 1.039% titrated acids; total lactic acid bacteria 4,06 x 1010cfu / ml and mean inhibitory diameter 13,10 mm (moderate resistance) to E. Coli and 13,91 mm (moderate resistance) to S. thypi with ANOVA test (P < 0,05) so that synbiotic yoghurt yellow pumpkin has activity as antibacterial. Keywords: Antibacterial, Yellow Pumpkin , Synbiotic Yoghurt.